Common and Distinctive Features of the Image of Women in the Mythology of the Peoples of the World through the Translated Legends of Aziz Gardi - Sdiq Awrahman Ali; Naz Ahmed Saeed; Thuraya Ahmed Abdulla (Zanco Journal of Human Sciences, 2024)
Myth, which originated from the earliest periods of human life, is the product of the first steps of human thought, and therefore is regarded as a heritage of human thought. Myth is a human attempt to know himself and understand the phenomena around him, to interpret and interpret them. Myths of nations generally carry thoughts and beliefs, aspirations and desires, fears, superstitions and religious beliefs of the past. One of the windows through which we get acquainted with the legends of the world's nations is the translated works of the late Aziz Gardi, who has translated many legends of the world's nations into the sweet Kurdish language. Through Aziz Gardi's translated works, we have tried to make a comparison between: African, German, Turkish and Gapan mythology. We have taken the image and character of women as an example. In this study, we want to answer the question whether all the nations of the world are depicted as the same female character in mythology, or whether they are different, whether the artistic structure of mythology is the same or different. In this study, we will look for common links between the legends of these peoples. We will also identify their differences. Finally, we present the results obtained.